The natural resources of the garifuna of Orinoco Nicaragua / Robert H. Horwich - Horwich, Robert H. (1996)
A short history o Orinoco, fishing Miss Melida González, Mr. Ramon Martinez, Farming Miss Bernice Estrada, Mr. Alejandro Sambola, hunting Mr. Leopoldo Flores, Mr. Guillermo López, timber Mr Sam Gonzalez, Mr. Martin Velazquez, Bush medicine, Mr. Jacinto Sambola, Miss Pualina Hebbert.